2016
DOI: 10.3389/fpls.2016.01811
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Tetrapyrrole Biosynthesis in Arabidopsis thaliana

Abstract: Biosynthesis of chlorophyll (Chl) involves many enzymatic reactions that share several first steps for biosynthesis of other tetrapyrroles such as heme, siroheme, and phycobilins. Chl allows photosynthetic organisms to capture light energy for photosynthesis but with simultaneous threat of photooxidative damage to cells. To prevent photodamage by Chl and its highly photoreactive intermediates, photosynthetic organisms have developed multiple levels of regulatory mechanisms to coordinate tetrapyrrole biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 165 publications
(262 reference statements)
3
88
1
Order By: Relevance
“…The function of GRMZM5G888696 was further supported by a pleiotropic QTL that was detected in two independent RIL populations (ZHENG58/SK and DAN340/K22) (Tables S2 and S7). GRMZM2G024739 was significant for GT and TT, and its orthologue, CRY1, has been reported to regulate chlorophyll biosynthesis (Kobayashi and Masuda, 2016;McCormac and Terry, 2002;Stephenson and Terry, 2008). Furthermore, we found that natural variations in fatty acid pathway genes affect phenotypic variation in tocopherol content, which is supported by at least four points of evidence.…”
Section: Identification Of Nontocopherol Pathway Genes In Controllingsupporting
confidence: 74%
See 2 more Smart Citations
“…The function of GRMZM5G888696 was further supported by a pleiotropic QTL that was detected in two independent RIL populations (ZHENG58/SK and DAN340/K22) (Tables S2 and S7). GRMZM2G024739 was significant for GT and TT, and its orthologue, CRY1, has been reported to regulate chlorophyll biosynthesis (Kobayashi and Masuda, 2016;McCormac and Terry, 2002;Stephenson and Terry, 2008). Furthermore, we found that natural variations in fatty acid pathway genes affect phenotypic variation in tocopherol content, which is supported by at least four points of evidence.…”
Section: Identification Of Nontocopherol Pathway Genes In Controllingsupporting
confidence: 74%
“…The function of GRMZM5G888696 was further supported by a pleiotropic QTL that was detected in two independent RIL populations (ZHENG58/SK and DAN340/K22) (Tables S2 and S7). GRMZM2G024739 was significant for GT and TT, and its orthologue, CRY1 , has been reported to regulate chlorophyll biosynthesis (Kobayashi and Masuda, ; McCormac and Terry, ; Stephenson and Terry, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faulty regulation is potentially lethal due to release of photosensitizing intermediates such as protoporphyrin IX (PPIX) or Mg-protoporphyrin IX (Mg-PPIX) in the presence of oxygen and light (Rebeiz et al, 1990;Mochizuki et al, 2010;Busch and Montgomery, 2015). Heme and chlorophyll biosynthesis in plants and algae share a trunk pathway in which PPIX is derived from the amino acid glutamate (reviewed in Grossman et al, 2004;Tanaka and Tanaka, 2007;Kobayashi and Masuda, 2016). PPIX is the penultimate intermediate in both pathways, which diverge upon addition of either Fe 2+ for heme or Mg 2+ for chlorophyll ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, during development under either short day conditions or in continuous light, ASC and sGluTR correlated and peaked after two weeks. GluTR levels and activity are known to be low in darkgrown plants but to massively increase upon illumination and, inversely, to diminish when lightgrown plants are transferred to extended darkness (Kobayashi and Masuda 2016). The authors analyzed the distribution of GluTR between stroma and membrane fraction under such conditions.…”
mentioning
confidence: 99%